Transdermal patches loaded with L-cysteine HCL as a strategy for protection from mobile phone emitting electromagnetic radiation hazards - Samia M. Omar; Mohamed Nasr; Diana A. Rafla (Elsevier, 2019)
Mobile phone usage has been increased in the last few years emitting electromagnetic radiation (EMR), which disturbs normal cellular processes via oxidative stress. L-cysteine, a glutathione precursor, prevents oxidative damage. Transdermal patches (TDPs) loaded with L-cysteine hydrochloride (L-CyS-HCL) were fabricated by dispersion of L-CyS-HCL 5% w/w and different concentrations of sorbitol as a plasticizer in room-temperature vulcanizable synthetic silicone matrices (RTV-Si). The effect of sorbitol on patch physicochemical parameters was assessed; in-vitro L-CyS-HCL release profiles and ex-vivo permeation were studied. Pharmacokinetic parameters of endogenous synthetized in-vivo glutathione, after receiving IV bolus dose of L-CyS-HCl and L-CyS-HCl-RTV-Si-TDPs were studied in rat model. The influence of L-CyS-HCL-RTV-Si-TDPs against damaging effects of mobile phone EMR on rats' blood and brain tissues was studied. The results revealed that patch plasticity, intensity reflections, surface porosity, L-CyS-HCL release rate and skin permeation increased with increasing sorbitol concentration. Pharmacokinetic profile for IV dose and L-CyS-HCl-RTV-Si-TDPs revealed that the L-CyS-HCl-RTV-Si-TDPs provided a sustained glutathione plasma concentration-time profile over entire patch application. High significant differences in biological parameters (blood and brain samples) were observed for radiated rats using the patch in study compared with positive control rats. Promising long-term strategy for protection against mobile phone hazards was obtained. Keywords: Electromagnetic radiation, Mobile phone hazards, L-cysteine, Transdermal patches, Silicone transdermal patches, Glutathione